Adolescents’ fight against the negative effects of the Covid-19 social lockdown: case of Culiacán, Sinaloa, México - Pineda Castillo, Kristian Armando (IE Revista de Investigación Educativa de la REDIECH, 2022)
This investigation had the purpose of enhancing the life and educational experience of adolescents by executing a healthy life plan with the participation of a high school community. Various theoretical aspects played a significant role in the decisions made, starting from the major coronavirus preventive measures all the way to the healthy lifestyles that could be adopted to face the pandemic. A qualitative approach was embarked on under an action research design throughout six months employing techniques such as participant observation, online questionnaires, in-depth interviews, and focus groups to collect information from 123 participants. The results demonstrated how the intervention favored the lifestyles in physical, emotional, educational, and social dimensions, as well as the prevention of destructive thoughts. Additionally, most teenagers, teachers, and principals expressed satisfaction with the implementation of the project. It can be concluded that united actions ought to be put through to deal with different social problematics, which is a valid rationale to opt for collaborative actions in the education field that impact society in general.